Penerapan Fish Bowl Technique untuk Meningkatkan Aktivitas Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas V Sekolah Dasar Negeri 005 Empat Balai Kuok - Revi Dahlianti (Milenial: Journal for Teachers and Learning, 2023)
This study aims to determine the increase in the results of student learning activities in natural science subjects through the application of the fish bowl technique for class V State Elementary School 005 Empat Knok Hall. teachers and only a few students who are active in learning, this research is a classroom action research. The subjects in this study were one teacher and 28 students at the 005 Empat Kuok State Elementary School. The object of this study was the fish bowl technique and learning activities. This research was conducted in two cycles and each cycle consisted of two meetings. The technique of collecting is using observation and documentation techniques. Meanwhile, the data analysis technique used is descriptive analysis with percentages. Based on the results of research and data analysis shows that the application of the fish bowl technique can improve student learning activities. It is known that before the action was taken, an average of 54.91% was obtained or was in the less high category. Then after the application of the fish bowl technique in the first cycle, the first meeting only reached 59.97% or was in the high enough category, at the second meeting it reached 62.20% or was in the high enough category. In the second cycle of the first meeting, student learning activities increased, namely 72.32% or were in the fairly high category at the second meeting reaching 79 16% or were in the high category. This means that it has reached the established success indicators. Thus it can be concluded that the application of the fish bowl technique can improve student learning activities